Cannabinoid as Pain Modulation: The Review - Saikia, Deepjyoti (Journal of Drug Delivery and Therapeutics, 2022)
Cannabinoids are the most commonly recognized herbal plant, having much medicinal importance from ancient times and plays an important role in Indian culture. Now a day’s cannabinoids are used for many therapeutic purposes, and under clinical trial by various institutions. In the latest discovery within humans, it was found that we also have cannabinoids, receptors, and enzymes in our body, so it is termed as endocannabinoids, it consists of receptors CB1 and CB2, endocannabinoids and their enzyme. Most of the phyto-cannabinoids work in these receptors, which result in Ant inflammatory, analgesic, antioxidant, antiemetic, antifungal, antibiotic, AChE inhibitor. The most common effect shown is pain modulation, in this article we are getting into various methods by which phyto-cannabinoids modulate pain signals in our body and all the clinical trial which is ongoing or complicated the trial on cannabis.Keywords: Tetrahydrocannabinol (THC), CANNABINOIDS, Endocannabinoid system (ECS), Excitatory postsynaptic potential (EPSP).